The level of employees satisfaction after the merger of Bank Bumiputra (BBMB) and commerce Asset Holding Berhad (CAHB) / Siti Ensah Mokhtar ... [et al.] - Mokhtar, Siti Ensah (2002)
Merger is not a new thing that happened in our country. The mergers not only in the banking sector but in most industries are painful, tedious, time consuming and more often than not, do not produce the desired results. Due to the implemented of AFTA, our government had proposed the merger with aim to combined 58 Malaysia financial institutions into six banking groups to enhance efficiency and prepare Malaysia for global competition. Doing bank mergers, rises the pro's and con's where Bank Negara Malaysia (BNM) has stated clearly that the mergers will prepare the local banks for eventual liberalization. As Malaysia prepares for greater degrees of liberalization in its financial system, consolidation in banking will have to be the driving force in this decade. The creation of large banking groups should certainly help to encourage competition and create shareholder value for investor. The merging of Bank Bumiputra Malaysia Berhad and Commerce Asset-Holding Berhad (CAHB) had spawned the country's second largest commercial bank with RM 70 billion of total asset. The new bank is known as Bumiputera Commercial Bank Berhad (BCB). Since the merger tok place, about 11000 of total staff have been involved. As Dr. Rozali, the Commerce Asset — Holding Berhad (CAHB) executive Director said there are occur some attrition but this rules out massive retrenchment. One consequence of this merger is the existence of the new Islamic Bank that helps to absorb 500 to 1000 employees.